A Plant-Specific TGS1 Homolog Influences Gametophyte Development in Sexual Tetraploid Paspalum notatum Ovules - Carolina Colono; Juan Pablo A. Ortiz; Hugo R. Permingeat; Eduardo Daniel Souza Canada; Lorena A. Siena; Nicolás Spoto; Florencia Galdeano; Francisco Espinoza; Olivier Leblanc; Silvina C. Pessino (Frontiers in Plant Science, 2019)
Aposporous apomictic plants form clonal maternal seeds by inducing the emergence of non-reduced (2n) embryo sacs in the ovule nucellus and the development of embryos by parthenogenesis. In previous work, we reported a plant-specific TRIMETHYLGUANOSINE SYNTHASE 1 (TGS1) gene (PN_TGS1-like) showing expression levels positively correlated with sexuality rates in facultative apomictic Paspalum notatum. PN_ TGS1-like displayed contrasting in situ hybridization patterns in apomictic and sexual plant ovules from premeiosis to anthesis. Here we transformed sexual P. notatum with a TGS1-like antisense construction under a constitutive promoter, in order to produce lines with reduced transcript representation. Antisense plants developed prominent trichomes on the adaxial leaf surface, a trait absent from control genotypes. Reproductive development analysis revealed occasional formation of twin ovules. While control individuals typically displayed a single meiotic embryo sac per ovule, antisense lines showed 12.93–15.79% of ovules bearing extra nuclei, which can be assigned to aposporous-like embryo sacs (AES-like) or, alternatively, to gametophytes with a misguided cell fate development. Moreover, around 8.42–9.52% of ovules showed what looked like a combination of meiotic and aposporous-like sacs. Besides, 32.5% of ovules at early developmental stages displayed nucellar cells with prominent nuclei resembling apospory initials (AIs), which surrounded the megaspore mother cell (MMC) or the MMC-derived meiotic products. Two or more concurrent meiosis events were never detected, which suggest a non-reduced nature for the extra nuclei observed in the mature ovules, unless they were generated by proliferation and misguided differentiation of the legitimate meiotic products. The antisense lines produced a similar amount of viable even-sized pollen with respect to control genotypes, and formed an equivalent full seed set (∼9% of total seeds) after self-pollination. Flow cytometry analyses of caryopses derived from antisense lines revealed that all full seeds had originated from meiotic embryo sacs (i.e. by sexuality). A reduction of 25.55% in the germination percentage was detected when comparing antisense lines with controls. Our results indicate that PN_ TGS1-like influences ovule, gametophyte and possibly embryo development.